Field Performance of a Constructed Litter Trap with Oil and Grease Filter using Low-cost Materials - Rahmat, Siti Nazahiyah; Adel Ali Saeed Abduh, Algheethi; Mohd Ali, Ahmad Zurisman; Mohammad Razi, Mohd Adib; Adnan, Mohd Shalahuddin (International Journal of Integrated Engineering, 2018)
The current study was conducted to develop a litter trap by using crushed clay as an adsorbent media filter to reduce oil and grease (O&G) contents in residential wastewater and then to prevent the degradation of the environment and natural water bodies. Clay acts as a magnet, drawing the oil molecules out of the water and causing them to attach to the surfaces of the clay. The trap was built using Polyvinyl chloride (PVC) pipe and bamboo and installed at site-specific discharge points of storm water for removal of O&G. A total of twenty-four (24) wastewater samples were collected before and after the filtration The design achieved 94% of O&G removal. However, the removal efficiency deepened on the rainfall intensity, the increasing of rainfall effect negatively on the removal percentage of O&G. Nonetheless, the designed system exhibited a potential to remove O&G from the residential wastewater.